Experimental Evidence of A2A–D2 Receptor–Receptor Interactions in the Rat and Human Carotid Body - Stocco, Elena; Sfriso, Maria Martina; Borile, Giulia; Contran, Martina; Barbon, Silvia; Romanato, Filippo; Macchi, Veronica; Guidolin, Diego; De Caro, Raffaele; Porzionato, Andrea (Frontiers in Physiology, 2021)
Adenosine A2A receptors (A2AR) and dopamine D2 receptors (D2R) are known to be involved in the physiological response to hypoxia and their expression/activity may be modulated by chronic sustained or intermittent hypoxia. To date, A2AR and D2R can form transient physical receptor-receptor interactions (RRIs) giving rise to a dynamic equilibrium able to influence ligand binding and signaling, as demonstrated in different native tissues and transfected mammalian cell systems. Given the presence of A2AR and D2R in type I cells, type II cells and afferent nerve terminals of the carotid body (CB), the aim of this work was to demonstrate here, for the first time, the existence of A2AR-D2R heterodimers by in situ proximity ligation assay (PLA). Our data by PLA analysis and tyrosine hydroxylase/S100 colocalization indicated the formation of A2AR-D2R heterodimers in type I and II cells of the CB; the presence of A2AR-D2R heterodimers also in afferent terminals is also suggested by PLA signal distribution. RRIs could play a role in CB dynamic modifications and plasticity in response to development/aging and environmental stimuli, including chronic intermittent/sustained hypoxia. Exploring other RRIs will allow for a broad comprehension of the regulative mechanisms these interactions preside over, with also possible clinical implications.